Mental-Health Phenotypes and Patient-Reported Outcomes in Upper-Extremity Illness. (4th August 2021) - Miner, Harrison; Rijk, Léon; Thomas, Jacob; Ring, David; Reichel, Lee M.; Fatehi, Amirreza
Abstract : Background: Prior studies have suggested that misconceptions (i.e., unhelpful thoughts or cognitive errors resulting from cognitive bias) and distress (symptoms of anxiety or depression) are key factors associated with variation in health, as quantified with use of patient-reported outcome measures. The primary purpose of the present study was to identify mental-health phenotypes (i.e., combinations of various types of misconceptions and distress) that might help direct care and to test for differences in magnitude of activity tolerance, pain intensity, and self-efficacy in response to pain between phenotypes. We also studied demographic factors and diagnostic categories associated with mental-health phenotypes. Methods: In a cross-sectional study, 137 patients seeking upper-extremity musculoskeletal specialty care completed a survey including demographics, mental-health questionnaires, and measures of upper-extremity-specific activity tolerance, pain intensity, and pain self-efficacy. We used cluster analysis to identify groups of patients with similar phenotypes. We used analysis of variance testing to assess differences in activity tolerance, pain intensity, and pain self-efficacy among phenotypes. Results: The cluster analysis yielded 4 unique mental-health phenotypes, which fit the theoretical conceptualizations of "low misconception and low distress, " "notable misconception, " "notable depression and notable misconception, " and "notable anxiety, depression, and misconception." Patients with low bias and low distress had significantly greater activity tolerance and greater pain self-efficacy than the other phenotypes, as well as a significantly lower pain intensity than phenotypes with notable distress. Conclusions: Cluster analysis of mental-health questionnaire data can identify mental-health phenotypes that are associated with greater activity tolerance and pain intensity. This approach might help clinicians to strategize and prioritize approaches that correct unhelpful thoughts and ameliorate symptoms of distress among patients seeking musculoskeletal specialty care. Such strategies have the potential to achieve more comprehensive, whole-person care, more selective operative treatment, and improved outcomes. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.